Association between Nursing Care Quality and Amount of Violence against Nurses in Emergency Departments - Mitra Rasteh; Mahbobeh Abdolrahimi; Maliheh Nasiri; Mahnaz Ilkhani (Iranian Journal of Nursing and Midwifery Research)
Background: Nursing care quality is among the most important criteria influencing patient satisfaction. Violence against nurses has been proposed as a global problem in health settings. Thus, we aimed to examine the association of nursing care quality with the amount of violence against nurses to provide authorities with information for planning the provision of higher-quality nursing care and reducing violence. Materials and Methods: This descriptive study analyzed descriptive and inferential statistics using demographic information, the Nursing Care Quality Questionnaire, and Workplace Violence in the Health Sector Questionnaire. Using the convenience sampling method, 120 nurses and 120 patients in emergency departments in 2022 were selected as the study participants. Results: The results showed that 56.70% of patients reported the nursing care quality level as “favorable,” 40.80% as “somewhat favorable,” and 2.50% as “unfavorable.” The prevalence of nurses’ exposure to verbal, physical, sexual, and racial violence was 96.70%, 50.00%, 12.50%, and 10.00%, respectively. The Mann–Whitney test showed a significant association between sexual violence and the physical dimension of nursing care quality (P < 0.05). However, nurses’ and patients’ demographic variables were not correlated with violence against nurses, and nursing care quality, respectively (P > 0.05). Conclusions: Nurses who had faced sexual violence had a lower nursing care quality score in the physical dimension including education, safety, and pain control. Therefore, it is suggested that the impact of nurse training in the above-mentioned fields on the frequency of violence against nurses be investigated.